2006
DOI: 10.1038/sj.leu.2404459
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib in relapsed multiple myeloma: response rates and duration of response are independent of a chromosome 13q-deletion

Abstract: Studies of bortezomib in patients with relapsed multiple myeloma (MM) suggested that bortezomib may be active even in the presence of adverse prognostic factors. We therefore evaluated 62 patients with relapsed/refractory MM who were treated with single-agent bortezomib, and addressed the question whether or not the negative prognostic impact of unfavorable cytogenetic abnormalities may be overcome by bortezomib. By interphase fluorescence in situ hybridization (FISH), a deletion of chromosome 13q14 [del(13q14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(49 citation statements)
references
References 26 publications
4
45
0
Order By: Relevance
“…In relapsed or refractory MM patients with del(13), outcomes reported here for lenalidomide and dexamethasone are comparable with those reported for bortezomib in a consecutive patient Lenalidomide and cytogenetics in myeloma H Avet-Loiseau et al cohort (ORR 45%; OS 9.9 months) 17 and in a retrospective analysis of the SUMMIT (ORR 24%; OS 10.0 months) and APEX (ORR 20-53%; OS 10.0 months to not reached) trials. 18 In the consecutive patient cohort, the authors reported no significant difference in outcomes between patients with and without del(13); however, median time from initiation of first-line therapy was significantly shorter in patients with than without del(13) (26 months vs 51 months; P ¼ 0.02).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In relapsed or refractory MM patients with del(13), outcomes reported here for lenalidomide and dexamethasone are comparable with those reported for bortezomib in a consecutive patient Lenalidomide and cytogenetics in myeloma H Avet-Loiseau et al cohort (ORR 45%; OS 9.9 months) 17 and in a retrospective analysis of the SUMMIT (ORR 24%; OS 10.0 months) and APEX (ORR 20-53%; OS 10.0 months to not reached) trials. 18 In the consecutive patient cohort, the authors reported no significant difference in outcomes between patients with and without del(13); however, median time from initiation of first-line therapy was significantly shorter in patients with than without del(13) (26 months vs 51 months; P ¼ 0.02).…”
Section: Discussionsupporting
confidence: 81%
“…18 In the consecutive patient cohort, the authors reported no significant difference in outcomes between patients with and without del(13); however, median time from initiation of first-line therapy was significantly shorter in patients with than without del(13) (26 months vs 51 months; P ¼ 0.02). 17 In the retrospective analysis, prognosis appeared to be poorer in patients with del(13) in both studies, but the differences were not statistically significant in the matched-pairs analyses (selected groups of patients balanced for age and ISS parameters). 18 Our study adds new data with regard to the prognostic value of high-risk cytogenetic abnormalities in relapsed or refractory MM treated with novel therapies.…”
Section: Discussionmentioning
confidence: 75%
“…Our results could also be explained by the recent availability over our study period of time of novel therapeutic agents at the time of the relapse. Preliminary data suggest that bortezomib 26 or lenalidomide 27 could be the treatment of choice in this situation. New targeted therapies such as FGFR3 inhibitor currently evaluated in prospective protocols could also improve the outcome of this aggressive disease in patients expressing FGFR3.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies in the relapsed setting, bortezomib has been shown to be active with a similar toxicity profile in patients with chromosome 13 deletion [32,33], and in patients with renal dysfunction or renal failure requiring dialysis [34 -36].…”
Section: Introductionmentioning
confidence: 99%